Family Communication Patterns in Gender Relations in Coastal and Mountain Communities in Aceh - Marhamah; Irwanto; Fauzi; Shafira Ulfa Rahmani; Sufri Eka Bhakti (MUWAZAH : jurnal kajian gender, 2022)
This study explores the dynamics of gender relations and family communication patterns in coastal and mountain communities in Aceh to understand how family harmony is maintained in different socio-geographical contexts. Employing a qualitative phenomenological approach, data were collected through interviews, observations, focus group discussions, and documentation involving 20 families—10 from North Aceh District and 10 from Central Aceh District. This research is grounded in the analysis of gender partnership concepts and communication orientation theories. Data validation employed source triangulation, and analysis was conducted using the Miles and Huberman model, including data reduction, display, and verification. The findings reveal that mountain communities implement gender partnership models in the division of domestic and public roles, promoting equality. In contrast, coastal communities maintain a more traditional division of roles, with women in domestic and men in public spheres, albeit adaptively. Decision-making predominantly remains with male heads of families in both communities, though collaborative consultation is evident. Communication patterns differ: coastal communities display patterns of equality and imbalanced separation, whereas mountain communities emphasize balanced separation through traditional practices like manganese iyo. These patterns foster mutual understanding, openness, and trust, contributing significantly to family harmony and reducing divorce rates.